BREAST CANCER PERCEPTION IN A GROUP OF WOMEN IN A HOSPITAL IN POPAYÁN, COLOMBIA - Molano-Tobar, Nancy Janneth (2017)
The objective of this paper was to identify the perception of breast cancer in a group of women in the city of Popayán, Colombia. Methodology. A qualitative study was conducted, applying techniques such as observation and in-depth interviews with semi-structured questionnaires, audio recordings, and logs. Fieldwork was conducted between periods I and II of 2015. A total of 39 female patients participated with an average age of 46.70 years, who were diagnosed with stage II breast cancer and were being treated at Hospital Universitario San José, City of Popayan, Colombia. Results. Four categories were obtained: cancer as an inherited disease; anxiety and depression for the future; physical and sexual dissatisfaction; and family as essential support. Conclusions. From the public health perspective, breast cancer is a high-risk disease, both economically and socially. From an individual perspective, it generates feelings of anxiety and depression in women, leading to doubts about their future and fear to pass it to their children. A particularity that manifested was body insecurity and dissatisfaction, which affects their social and romantic relationships, deteriorates their self-esteem, self-confidence and emotional vulnerability and affects the quality of life of this population. Consequently, it is important to have an interdisciplinary team to support the different situations faced by women and their families.